Menerapkan Model Pembelajaran Project Based Learning Dalam Meningkatkan Hasil Belajar Siswa di Sman 9 Padang - Arbian, Arbian (Jurnal Pendidikan Tuntas, 2024)
This study aims to determine whether the application of the PBJL method in improving the learning outcomes of class X students of Islamic religion subjects on the aspect of Knowing adultery and promiscuity to maintain human dignity. The subjects in this study were class X at SMAN 9 Padang. This research is a Classroom Action Research (PTK) which consists of 2 cycles, namely cycle I, cycle II. Each cycle is a series of activities, each of which consists of 4 stages of planning, implementation of observation / observation and reflection. This Classroom Action Research uses data collection methods, namely oral tests, observation sheets and documentation. The data analysis used by comparing the achievement of learning outcomes for each cycle is marked by an increase in the minimum completeness criteria (KKM) or using qualitative descriptive. The results obtained from this study are an increase in the learning outcomes of class X students of Islamic religious education subjects in the aspect of the Qur'an strengthening harmony through tolerance. The class average at the pre-cycle stage was 6.78, in cycle I it rose to 75.89 in cycle II it increased again to 83.75. Classical completeness at the pre-cycle stage was 22.2% in cycle 1 to 75.89, in cycle I it increased again to 75.4%, in cycle II it increased again to 83.75%. Based on these learning results, it can be concluded that through the Project Based Learning method can improve the learning outcomes of class X students in the field of Islamic Religious Education in the aspect of the Qur'an the material of prohibition of adultery and promiscuity in the 2024-2025 school year.